2017
DOI: 10.1021/acs.jpcb.7b04163
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Basis for Inhibition of Calcium Phosphate Biomineralization by Osteopontin

Abstract: Calcium oxalate kidney stones form attached to Randall's plaques (RP), calcium phosphate (Ca-P) deposits on the renal papillary surface. Osteopontin (OPN) suppresses crystal growth in the complex process of urinary stone formation, but the inhibitory role of active domains of OPN involved in the initial formation of the RPs attached to epithelial cells has yet to be clarified. Here we demonstrate the thermodynamic basis for how OPN sequences regulate the onset of Ca-P mineral formation on lipid rafts as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Molecular-scale studies have further confirmed that the full-length OPN controls calcium oxalate surface crystallization kinetics . The OPN peptide segments have been shown to inhibit the onset of Ca–P mineral formation on membrane lipid rafts and the specific step growth of DCPD …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Molecular-scale studies have further confirmed that the full-length OPN controls calcium oxalate surface crystallization kinetics . The OPN peptide segments have been shown to inhibit the onset of Ca–P mineral formation on membrane lipid rafts and the specific step growth of DCPD …”
Section: Introductionmentioning
confidence: 86%
“…30 Molecular-scale studies have further confirmed that the full-length OPN controls calcium oxalate surface crystallization kinetics. 31 The OPN peptide segments have been shown to inhibit the onset of Ca−P mineral formation on membrane lipid rafts 32 and the specific step growth of DCPD. 33 In the present study, we selected a peptide segment having amino acid sequences from 93 to 106 of a full-length OPN protein with highly conserved aspartic acid residues (DDVDDTDDSHQSDE) to investigate the role of an OPN peptide segment in influencing the phase transformation of DCPD to HAP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ordered organic/inorganic hybrid structures have been produced through biomineralization-inspired approaches using acidic water-soluble organic molecules and/or water-insoluble polymer templates. , Cooperative effects between soluble and insoluble organic polymers lead to the formation of hierarchically ordered structures, similar to biominerals. Although there are many examples of organic additives that have been designed for the development of ordered hybrid materials, controlling ordered structures on the nano- to macroscale has not been achieved yet. This is largely because the role of the organic components in hybrids is not well understood, especially the role of insoluble templates.…”
Section: Introductionmentioning
confidence: 99%
“…5 As the initial nidus, 7−9 DCPD may drive the CaO x nucleation in Randall's plaque. 5 The inhibitors known to prevent stone formation include proteins, 10 peptides, 11,12 and small organic molecules. 10,13,14 Inhibitor-crystal recognition and interaction influence both the initial formation of metastable nuclei 15,16 and the stable mineral phase with different crystallites and sizes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The inhibitors known to prevent stone formation include proteins, peptides, , and small organic molecules. ,, Inhibitor-crystal recognition and interaction influence both the initial formation of metastable nuclei , and the stable mineral phase with different crystallites and sizes. , Moreover, inhibitors modify morphological features of the calcified tissues . It is well accepted that the basic mode of action for inhibitors to modulate mineralization is to impede solute molecule attachment through the initial site-specific adsorption on crystal surfaces, , subsequent incorporation, , and inclusion inside the crystal. As the adsorbed inhibitor exhibits stronger competition with solute ions or molecules, it may permanently block kink sites along the advancing steps, thereby slowing the step movement velocity and interfering with or preventing crystal layer growth.…”
Section: Introductionmentioning
confidence: 99%